PS 17-02 TARGET ORGAN DAMAGE OF PRIMARY ALDOSTERONISM DIFFERENT SUBTYPES. (September 2016) - Zhang, Ying; Song, Wei; Cheng, Yunpeng; Guo, Ran; Lu, Yan; Yang, Xiaolei; Jiang, Yinong
Abstract : Objective: To calculate the coincidence rate of CT diagnosis primary aldosteronism subtypes, and to determine the difference of the target organ damage between two subtypes primary aldosteronism (APA and IHA). Design and method: 90 cases of primary aldosteronism and 60 cases of primary hypertension in our hospital were summarized from 2009 to 2015.The cases were retrospectively analyzed, by CT and surgical pathology identified subtypes, and calculated the coincidence rate of CT diagnosis. The organ damage was evaluated by left ventricular mass index(LVMI) and urinary albumin creatinine ratio(UACR). Results: In 90 cases of primary aldosteronism, the coincidence rate of CT was 84.4%. LVMI and UACR in patients with primary aldosteronism was higher than that in EH group, but there was no significant difference between APA group and IHA group. Conclusions: There was no significant difference between the APA group and the IHA group in organ damage. And the damage was more serious in patients with primary aldosteronism than with essential hypertension. The coincidence rate of CT in the diagnosis of primary aldosteronism was acceptable.